Universal health coverage, health systems strengthening, and the World Bank. (31st August 2017) - Tichenor, Marlee; Sridhar, Devi
Abstract : In the second article of the series, Marlee Tichenor and Devi Sridhar discuss how the World Bank is promoting better access to healthcare